2021
DOI: 10.3892/etm.2021.10512
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑195‑5p suppresses the proliferation, migration, invasion and epithelial‑mesenchymal transition of laryngeal cancer cells in vitro by targeting E2F3

Abstract: Increasing evidence has indicated that microRNAs (miRNAs/miRs) play an important role in the occurrence and development of various types of cancer. The aim of the present study was to investigate the role and underlying molecular mechanisms of miR-195-5p in laryngeal cancer cell proliferation, migration and invasion. Reverse transcription-quantitative PCR (RT-qPCR) was performed to measure the expression levels of miR-195-5p in laryngeal carcinoma cell lines. The expression levels of miR-195-5p and E2F transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…CircPVT1 has been proved to locate mainly in cytoplasm, which meant that it might act as microRNA sponges to regulate downstream gene expression. MiR-195 is dysregulated in several tumors, such as colon cancer [ 56 ], non-small lung cancer [ 57 ], laryngeal cancer [ 58 , 59 ], gastric cancer [ 60 ], cervical cancer [ 61 ], colorectal cancer [ 62 ], breast cancer [ 63 ], lung adenocarcinoma [ 64 ] and osteosarcoma [ 65 ]. Moreover, miR-195 has been demonstrated that play a significant role in PTC [ 66–69 ].…”
Section: Discussionmentioning
confidence: 99%
“…CircPVT1 has been proved to locate mainly in cytoplasm, which meant that it might act as microRNA sponges to regulate downstream gene expression. MiR-195 is dysregulated in several tumors, such as colon cancer [ 56 ], non-small lung cancer [ 57 ], laryngeal cancer [ 58 , 59 ], gastric cancer [ 60 ], cervical cancer [ 61 ], colorectal cancer [ 62 ], breast cancer [ 63 ], lung adenocarcinoma [ 64 ] and osteosarcoma [ 65 ]. Moreover, miR-195 has been demonstrated that play a significant role in PTC [ 66–69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, miRNAs act as suppressors of proliferation and lymph-node metastasis and inducers of apoptosis, as in the cases of miR-141, miR-136-5p, miR-204-5p, miR-143-3p, miR-145-5p, and miR-144-3p [ 130 , 131 , 132 , 133 , 134 , 135 ]. Like miR-98, miR-625, and miR-195-5p, other microRNAs can reverse EMT [ 136 , 137 , 138 , 139 ]. Downregulation of miR-203 leads the laryngeal carcinoma cells to acquire stem-cell traits, such as CD44+ [ 139 ].…”
Section: Epithelial-to-mesenchymal Transition (Emt)mentioning
confidence: 99%
“…Knocking down Snail has been shown to enhance chemosensitivity [ 194 ]. In laryngeal carcinoma cell lines, successful attempts to reverse EMT have been made with the introduction of miRNAs [ 136 , 195 , 196 , 197 , 198 ], inhibitors of long-noncoding RNA [ 199 , 200 ], and flavonoids such as genistein, dihydroartemisinin, and brusatol [ 201 , 202 , 203 ]. Moreover, a higher expression of estrogen receptor-β has been found to correlate with lower EMT traits in laryngeal carcinoma.…”
Section: Epithelial-to-mesenchymal Transition—the Contemporary Approachmentioning
confidence: 99%
“…E2F3, which belongs to the E2F TF family, participates in cancer genesis and progression, and its expression is increased within diverse cancers like bladder cancer (BLCA), laryngeal cancer, osteosarcoma and breast cancer (BRCA) [26][27][28][29] . In addition, various miRNAs like miR-22, miR-194-5p or miR-195-5p, can regulate cancer genesis and progression via E2F3, suggesting that E2F3 may be the possible anticancer therapeutic target [30,26,27] . TargetScan online prediction identi ed E2F3 as miR-497-5p's potential target.…”
Section: Introductionmentioning
confidence: 99%